Metabolic and transcriptional analysis of tuber expansion in Curcuma kwangsiensis - Yunyi Zhou; Lixiang Yao; Yueying Xie; Baoyou Huang; Ying Li; Xueyan Huang; Liying Yu; Chunliu Pan (Scientific Reports)
Abstract The tubers of Curcuma kwangsiensis are regarded as an important medicinal material in China. In C. kwangsiensis cultivation, tuber expansion is key to yield and quality, but the regulatory mechanisms are not well understood. In this study, metabolomic and transcriptomic analyses were conducted to elucidate the mechanism underlying tuber expansion development. The results showed that auxin (IAA), jasmonic acid (JA), gibberellin (GA3), ethylene (ETH), and brassinolide (BR) levels increased during tuber expansion development. Metabolomic analysis showed that 197 differentially accumulated metabolites (DAMs) accumulated during tuber expansion development and these also play important roles in the accumulation of carbohydrates and secondary metabolites. 6962 differentially expressed genes (DEGs) were enriched in plant hormone signal transduction, starch and sucrose metabolism, linoleic acid metabolism, MAPK signaling pathway as well as sesquiterpenoid and triterpenoid biosynthesis. Comprehensive analysis revealed that DEGs and DAMs of plant hormone signal transduction, ABC transporters and biosynthesis of phenylpropanoids and terpenoids are critical pathways in regulating tuber expansion. In addition, some transcription factors (ARF, C2H2, C3H, NAC, bHLH, GRAS and WRKY) as well as hub genes (HDS, HMGR, ARF7, PP2CA, PAL and CCOMT) are also involved in this process. This study lays a theoretical basis for the molecular mechanism of tuber expansion in C. kwangsiensis.